Lectures on the History of Moral and Political Philosophy - Cohen, G. A. (Gerald Allan), 1941-2009 (Book collections on Project MUSE., 2013)
G.A. Cohen was one of the leading political philosophers of recent times. He first came to wide attention in 1978 with the prize-winning book Karl Marx's Theory of History: A Defence. In subsequent decades his published writings largely turned away from the history of philosophy, focusing instead on equality, freedom, and justice. However, throughout his career he regularly lectured on a wide range of moral and political philosophers of the past. This volume collects these previously unpublished lectures. Starting with a chapter centered on Plato, but also discussing the pre-Socratics as well as Aristotle, the book moves to social contract theory as discussed by Thomas Hobbes, John Locke, and David Hume, and then continues with chapters on Immanuel Kant, G.W.F. Hegel, and Friedrich Nietzsche.